Social Problems of Urban Planning (Results of Town-Building-Ecological Investigation in Kaunas) - Vanagas, Jurgis (Problemos, 1970)
The paper points out to insufficient account of social structure of urban population in working out town building projects and siting of service plants in particular. Population of all districts of the town is taken as integral totality and above-mentioned questions are solved by way of applying fairly generalized, unified standards. In social aspect population of separate districts of the town presents, however, a miscellaneous picture. The author analyses on the basis of the investigation carried out in Kaunas the reasons for uneven distribution of a number of negative social phenomena (alcoholism, breach of the peace, mental and venereal diseases) in the town. Intensity of the mentioned phenomena in separate districts of the town was confronted – by means of the methods of mathematical statistics – with parameters characterizing dwelling environment. Calculated coefficients of correlation exposed the close statistic link between the confronted indices. The author comes to the conclusion that the character of surroundings correlates with the intensity of social evils: the worse indices of dwelling environment, the greater the intensity of the latter. The paper presents concrete recommendations on improving the moral climate in the old-town part of Kaunas.